2015
DOI: 10.1111/ropr.12126
|View full text |Cite|
|
Sign up to set email alerts
|

State Renewable Energy Governance: Policy Instruments, Markets, or Citizens

Abstract: Since the 1990s, state governments in the U.S. have diversified policy instruments to encourage the electric power industry to deploy renewable sources for electricity generation. This study identifies the trends and variations in renewable energy policy governance among states and examines the effectiveness of policy instruments in the deployment of renewable energy sources for electricity production. This study explores 18 state legislative, renewable energy related

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
(165 reference statements)
0
21
0
Order By: Relevance
“…The literature emphasizes the role of country-specific political variables (Aklin & Urpelainen, 2013;Yi & Feiock, 2014) and of socio-technological factors (Park, 2015;Schaffer & Bernauer, 2014;Simmie, Sternberg, & Carpenter, 2014). Overall, the literature suggests that stable and comprehensive policy frameworks, cross-sectoral coordination, and close but transparent state-industry relations together with target education and research, demonstration and development (RD&D) programmes constitute factors that generate sustainable renewable energy development (Lipp, 2007;Negro, Alkemade, & Hekkert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The literature emphasizes the role of country-specific political variables (Aklin & Urpelainen, 2013;Yi & Feiock, 2014) and of socio-technological factors (Park, 2015;Schaffer & Bernauer, 2014;Simmie, Sternberg, & Carpenter, 2014). Overall, the literature suggests that stable and comprehensive policy frameworks, cross-sectoral coordination, and close but transparent state-industry relations together with target education and research, demonstration and development (RD&D) programmes constitute factors that generate sustainable renewable energy development (Lipp, 2007;Negro, Alkemade, & Hekkert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the level of public favorability toward various policy tools that could be adopted to address the FEW nexus is unclear. Studies have shown that most Americans favor reforming food policy [11], that they are willing to consider alternative energy policy options [12,13], and that they are concerned about policies affecting water quality [14]. However, to address food, energy, and water resources more effectively, it is imperative that research on public preferences and the explanations for those preferences be conducted from a nexus perspective.…”
Section: Public Opinion and Policy Preferencesmentioning
confidence: 99%
“…Wüstenhagen et al [41] × × × Hancock [35] × × × Betsill and Stevis [24] × × × Michalena and Hills [32] × × × × Hills and Michalena [33] × × Mazzucato and Semieniuk [34] × × × Park [42] × × × Notes: Government includes states, governments, public agencies, politicians, policy-makers, bureaucrats, local governments and sub-governmental organizations, etc. ; Public includes communities, households, families, residents, neighbors, civil societies, community groups and academia, etc.…”
Section: Narrow Renewable Energymentioning
confidence: 99%